Replanteando el concepto de justicia como equidad y velo de ignorancia en John Rawls desde el pluralismo ético - Huanca-Arohuanca, Jesús Wiliam (2022)
To examine the relationship between the concept of justice as an fairness and the veil of ignorance exposed by John Rawls within the transdisciplinarity of ethical pluralism, is transcendental in times where democracy, freedom and social contract are imperceptible tools for the domine doctrine of violence synthesized as neoliberalism. So there are three implications: The first analyzes equitable justice, considering that it is the first virtue of social institutions since the origin of the social contract developed by Hobbes, Locke, and Rousseau with certain structural modifications. The second examines how the original position as an abstract category should be operated under the veil of ignorance which in turn is formulated to ensure the fairness of justice. And the third tracks how ethical pluralism becomes an alternative to the gaps left by the philosopher in treatment, bearing in mind that each society has different moral systems for establishing justice and understanding the category of social contract.